Thyroidectomy: posterior neurovasculoglandular crossroads: pedicles, inferior, recurrent, parathyroid - Cazabán Perossio, Luis (Cirugía del Uruguay, 1973)
Surgical anatomy and operatory tactics in danger area in thyroid surgery recurrent nerve, inferior thyroid artery, parathyroid gland are analyzed. Recurrent nerve: Obligatory visual and palpatory identification helps reduce the number of permanent ¡'aralyses of vocal chords and makes possible safe hemostasis and gland resection. The danger of nervous lesions -regardless of quality of surgical technique employed-, is real in anatomical ( non recurrent inferior laryngeal nerve) and pathological (multinodular, endothoracic goiters) situations which distort normal path of nerve, displacing it forward. Inferior tl,yroid artery: Interruption of arterial flow by simple ligation, without section, at a distance f